Optimization of Skin Moisturizer Formula Based on Fixed Oil (VCO, Olive Oil, and Jojoba Oil): Optimasi Formula Pelembab Kulit Berbasis Minyak Nabati (VCO, Minyak Zaitun dan Minyak Jojoba) - Rakhma, Dita Nurlita; Nailufa, Yuyun; Ainun Najih, Yuli; Wahjudi, Hery (Akademi Farmasi Surabaya, 2021)
Currently, formulations of skin moisturizers are derived from natural compounds. Fixed oils are known to have compounds that potential to be developed as skin moisturizers based on emollient mechanism. Therefore, this study aims to determine the effect of oil type on the physical characteristics of skin moisturizer creams. In this study, a skin moisturizer cream was formulated using three types of fixed oils: VCO (F1), Olive Oil (F2), and Jojoba Oil (F3). All formulas were tested for physical characteristics of pH, cream type, viscosity, spreadability, and homogeneity. The test results show that all formulas appropriate to the skin pH range, have o/w type creams and homogeneous texture. In the results of the viscosity test, there was a significant difference (p<0.05) with the highest value of viscosity for F2 (16750 ± 250 cP) > F3 (14200 ± 346cP) > F1 (5833 ± 58 cP), while for spreadability test there were also significant differences (p<0.05) with the highest diameter for F1 (5.8 ± 0.1 cm) = F3 (5.7 ± 0.2 cm) > F2 (4.3 ± 0.2 cm). Based on the results, it can be concluded that the type of oil can affect the physical characteristics of the moisturizer formula. F1 and F3 have better physical characteristics than F2.